2002
DOI: 10.1042/bj20020574
|View full text |Cite
|
Sign up to set email alerts
|

Impaired trafficking of human kidney anion exchanger (kAE1) caused by hetero-oligomer formation with a truncated mutant associated with distal renal tubular acidosis

Abstract: Autosomal dominant distal renal tubular acidosis (dRTA) has been associated with several mutations in the anion exchanger AE1 gene. The effect of an 11-amino-acid C-terminal dRTA truncation mutation (901 stop) on the expression of kidney AE1 (kAE1) and erythroid AE1 was examined in transiently transfected HEK-293 cells. Unlike the wild-type proteins, kAE1 901 stop and AE1 901 stop mutants exhibited impaired trafficking from the endoplasmic reticulum to the plasma membrane as determined by immunolocalization, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 55 publications
3
70
1
Order By: Relevance
“…The pathogenetic mechanisms of these previously reported mutations remain unclear, functional studies having concluded that anion exchange is at worst only mildly diminished (4,6). It has been suggested that intracellular retardation of R589H and R901X mutants expressed in non-polarized cells is the dominant negative effect explaining the lack of urine acidification and dominant nature of dRTA (15,17). However, kAE1-R901X expression in MDCK cells grown to polarity clearly results in aberrant surface expression with some mutant protein appearing at the apical surface (19) in common with the findings reported here; on the other hand, Arg-589 mutants have yet to be assessed in polarized cells, and observed results for the different mutations may be different because of this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenetic mechanisms of these previously reported mutations remain unclear, functional studies having concluded that anion exchange is at worst only mildly diminished (4,6). It has been suggested that intracellular retardation of R589H and R901X mutants expressed in non-polarized cells is the dominant negative effect explaining the lack of urine acidification and dominant nature of dRTA (15,17). However, kAE1-R901X expression in MDCK cells grown to polarity clearly results in aberrant surface expression with some mutant protein appearing at the apical surface (19) in common with the findings reported here; on the other hand, Arg-589 mutants have yet to be assessed in polarized cells, and observed results for the different mutations may be different because of this.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired trafficking of mutant R589H, R589C, and R589S kAE1 proteins was demonstrated when expressed in HEK 293 cells, and co-expression of wild-type kAE1 with these mutant proteins also revealed a dominant negative effect (15). Furthermore, it has been suggested that the R901X mutant retained normal anion exchange activity in Xenopus oocytes but failed to express at the cell surface of unpolarized MDCK cells (16) and HEK 293 cells (17). From all of these data, it has been concluded that mutant AE1 proteins maintain sufficient anion transport function but are defective in targeting to the cell surface.…”
mentioning
confidence: 99%
“…In contrast, kAE1 901X and the R589H mutants expressed in 293 cells failed to exit the endoplasmic reticulum (28). The intracellular retention phenotype of kAE1 901X exhibited dominant negative properties in 293 cells (29), but these phenotypes differed in polarized epithelial cells (30). 2 The CA2 binding site of the AE1 C-terminal tail lies close to the terminus of the truncated dRTA mutant AE1 R901X, but the consequence of this truncation to Cl Ϫ /HCO 3 Ϫ exchange activity has not been tested.…”
mentioning
confidence: 99%
“…Other transient transfection studies also showed that kAE1 with R589H or R901Stop mutations is retained internally in HEK293 cells and that each of the mutant kAE1 proteins can hetero-oligomerise with the normal kAE1 protein (Quilty et al, 2002a;Quilty et al, 2002b). However, to fully characterise the effects of these mutations on kAE1 in the kidney and understand the basis of the kidney disease, it is important to investigate these mutations using a model system in which polarised targeting can be observed.…”
mentioning
confidence: 99%